1977
DOI: 10.4315/0362-028x-40.8.562
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fast Food Management Training Program: One Year Later

Abstract: This report summarizes an earlier short-term evaluation of a fast food restaurant manager training program and presents result from a re-evaluation approximately 1 year later. Thirty-one establishments in a single corporation were evaluated using criteria from the USPHS Food Service Sanitation Manual. Only 12 of the 31 original managers were still with the corporation 18 months after the start of the project. Those managers who participated in the training program tended to maintain or increase the sanitary qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In an evaluation of a fast food management training programme Jackson, Hatlen, and Palmer (1977), concluded that management training can be eVective if it is administered on a continuous basis, supported by the owners and includes frequent follow-up. Nabali et al (1986), concluded from their study that training of managers was eVective in improving hygiene standards.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of a fast food management training programme Jackson, Hatlen, and Palmer (1977), concluded that management training can be eVective if it is administered on a continuous basis, supported by the owners and includes frequent follow-up. Nabali et al (1986), concluded from their study that training of managers was eVective in improving hygiene standards.…”
Section: Discussionmentioning
confidence: 99%
“…The short‐and long‐term influences of management training in a fast‐food restaurant chain were assessed and reported in two stages[43,44]. Following an initial inspection to identify standards, the managers of 31 fast food restaurants were provided with in‐house hygiene training.…”
Section: Evaluations Of Courses In the Usamentioning
confidence: 99%